Case Report: Using Medtronic AP360 mechanical prosthesis in mitral valve replacement for patients with mitral insufficiency after primum atrial septal defect repair to reduce left ventricular outflow tract obstruction risk - Guo, Lei; Yang, Qiqi; Han, Yu; Zhao, Haige; Chen, Liangwei; Zheng, Junnan; Ni, Yiming (Frontiers in Surgery, 2023)
Background: Atrial septal defect is one of the most common congenital heart diseases in adults. Primum atrial septal defect (PASD) accounts for 4% to 5% of congenital heart defects. Patients with PASD frequently suffer mitral insufficiency, and thus, mitral valvuloplasty (MVP) or mitral valve replacement (MVR) is often required at the time of PASD repair. Unfortunately, recurrent unrepairable severe mitral regurgitation can develop in many patients undergoing PASD repair plus MVP in either short- or long-term after the repair surgery, requiring a re-do MVR. In those patients, risk of left ventricular outflow tract obstruction (LVOTO) has increased. Case presentation: We present 5 such cases who were aged from 24 to 47 years and had a PASD repair plus MVP or MVR for 14 to 40 years, suffering moderate to severe mitral regurgitation. Using Medtronic AP360 mechanical mitral prostheses, only one patient occurred mild LVOTO. Conclusions: Usage of Medtronic AP360 mechanical mitral prostheses to perform MVR in patients with MI who had a PASD repair history can potentially reduce the risk of LVOTO. Long-term follow-up is required to further confirm this clinical benefit associated with AP360 implantation in patients with PASD.